Transitivity Shift in Experiential Function of Texts in Official Website of Kementerian Kesehatan: - - Delia Zuhera (Edu-Ling: Journal of English Education and Linguistics, 2022)
The objectives of this research are to depict the shift of transitivity that happen brought about by applying interpretation strategies in the translation on the site of the Ministry of Health of the Republic of Indonesia. This research is Transitivity Shift In Experiential Function Of Texts In Official Website Of Kementrian Kesehatan. The sample of this research was clauses under the classification of experiential capacity that experience a shift intransitivity. The data were gathered by using the observation strategy, to be specific choosing the articles managing the Covid-19 and the English interpretation, perusing cautiously every one of the provisions in the source language, that is the Indonesian language, discovering the transitivity shift by grouping the sentences as per the experiential capacity function and were analyzed by qualitative descriptive method. The findings showed that there is a few transitivity shifts in the articles. In conclusion, the transitivity shift in two articles, there are one clause on the material to verbal, three clauses on the material to relational, two clauses on verbal to material, one clause on verbal to relational, and one clause on the material to existential. Nonetheless, there is no shift involving mental process in the two articles.